Comparative performance of ARIMA and DES models in forecasting electricity load demand in Malaysia - Miswan, Nor Hamizah; Mohd Said, Rahaini; Hussin, Nor Hafizah; Hamzah, Khairum; Ahmad, Emy Zairah (IJENS, 2016)
Malaysia is a developing country which is having a high level of energy demand. Load demand forecasting is essential that is also in line with increasing demand of electricity. The purpose of the current study is to compare the performance of two time series models in forecasting electricity load demand in Malaysia. Two methods are considered, which are Box-Jenkins Autoregressive Integrated Moving Average (ARIMA) and Double Exponential Smoothing (DES). Using Mean Absolute Percentage Error (MAPE) as the forecasting performance measure, the study concludes that ARIMA is more appropriate model.